HMGB1 Localization during Experimental Periodontitis - Boas Nogueira, Andressa Vilas [UNESP]; Chaves de Souza, Joao Antonio [UNESP]; Molon, Rafael Scaf de [UNESP]; Mariano Pereira, Elyne da Silva [UNESP]; Aquino, Sabrina Garcia de [UNESP]; Giannobile, William V.; Cirelli, Joni Augusto [UNESP] (Hindawi Publishing Corporation, 2014)
Aim. This study sought to investigate the in vitro expression profile of high mobility group box 1 (HMGB1) in murine periodontal ligament fibroblasts (mPDL) stimulated with LPS or IL-1 beta and in vivo during ligature-or LPS-induced periodontitis in rats. Material and Methods. For the in vivo study, 36 rats were divided into experimental and control groups, and biopsies were harvested at 7-30 d following disease induction. Bone loss and inflammation were evaluated. HMGB1 expression was assessed by immunohistochemistry, qPCR, and Western blot. Results. Significant increases in mPDL HMGB1 mRNA occurred at 4, 8, and 12 h with protein expression elevated by 24 h. HMGB1 mRNA expression in gingival tissues was significantly increased at 15 d in the LPS-PD model and at 7 and 15 d in the ligature model. Immunohistochemical staining revealed a significant increase in the number of HMGB1-positive cells during the experimental periods. Conclusion. The results show that PDL cells produce HMGB1, which is increased and secreted extracellularly after inflammatory stimuli. In conclusion, this study demonstrates that HMGB1 may be associated with the onset and progression of periodontitis, suggesting that further studies should investigate the potential role of HMGB1 on periodontal tissue destruction.